2014
DOI: 10.1371/journal.pone.0093010
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Breast Dynamic Morphological Changes after Dual-plane Augmentation Mammaplasty with 3D Scanning Technique

Abstract: BackgroundThe dual-plane technique has been widely used in augmentation mammaplasty procedures. However, there are some concerns about aesthetic contour maintenance for long time after muscle releasing. This study aims to track and analyze breast dynamic morphological changes after dual-plane breast augmentation with three-dimensional (3D) scanning technique.MethodsThirteen dual-plane anatomic implant augmentation patients underwent 3D scanning preoperatively (pre-OP) and postoperatively in four time points (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 29 publications
(39 reference statements)
3
21
0
Order By: Relevance
“…Summarized data from these studies are shown in Table 1 . Korea (7 series, 1380 cases) was the most represented nation, 12 , 15 , 17 , 19 22 followed by China (3 series, 622 cases), 14 , 16 , 23 Taiwan (1 series, 57 cases), 18 and Japan (1 series, 30 cases). 10 All studies were prospective and observational, and 3 offered comparative data.…”
Section: Resultsmentioning
confidence: 99%
“…Summarized data from these studies are shown in Table 1 . Korea (7 series, 1380 cases) was the most represented nation, 12 , 15 , 17 , 19 22 followed by China (3 series, 622 cases), 14 , 16 , 23 Taiwan (1 series, 57 cases), 18 and Japan (1 series, 30 cases). 10 All studies were prospective and observational, and 3 offered comparative data.…”
Section: Resultsmentioning
confidence: 99%
“…Breast volumes decreased from the first post-operative volume, and the final breast volume was reached between one and three months after surgery. A similar study was undertaken by Ji et al [93] using 3D-SI to investigate morphological changes after dual-plane augmentation mammoplasty. They found that sternal notchnipple distance was stable after one month, whereas nipple to IMF continued to increase until 6 months as volume redistributed from upper to lower pole.…”
Section: Quantifying Post-operative Changes Over Timementioning
confidence: 90%
“…3D imaging has also been used to investigate postoperative courses. Eder et al showed that posoperative changes after breast reduction continue for 3-6 months [33], and after breast augmentation for 3 months [34], while another group suggested 6 months [35]. Others have focused on symmetry, finding a high grade of breast asymmetry in general population [36], and in 92 out of 100 patients after augmentation [37].…”
Section: Breast Volumetry Is Of Key Importance In Breast Surgerymentioning
confidence: 99%